Exploring Sharia Screening Review in Islamic Capital Market in Indonesia (Jakarta Islamic Index) - Mustakim Muchlis; Hamid Habbe (LAA MAISYIR: Jurnal Ekonomi Islam, 2021)
Several previous studies on Islamic capital market screening have not conducted an in-depth exploration of Sharia screening on a country's index over different periods. This study aims to examine sharia screening performed on entities registered in the Jakarta Islamic (JII) Index 2015–2019. The study uses a descriptive quantitative approach by analyzing and describing Sharia screening in entities registered in JII. The research results show that the Financial Services Authority has properly screened Sharia law in registered entities according to the established criteria, as evidenced by looking at the qualitative aspects of entities that do not carry out activities that contain elements of usury, gharar, and maysir. Meanwhile, in the quantitative aspect, the entity has tracked the appropriateness between the percentage of interest-based debt of no more than 45 percent and non-halal income of no more than 10 percent. However, the OJK and MUI criteria still show some weaknesses compared to the screening criteria that apply in other countries